Da roça ao fogão - narrativas de (re)existências de famílias rurais do sul do Brasil na construção da agroecologia - Silva, Isabel Cristina Lourenço da (2021)
Agroecology is based on another scientific approach, promoting the dialogue of knowledge, and a scientific perspective that analyzes processes and not products. Agroecology promotes sustainable food systems, which highlight the social and political role of the subjects who reside in their territories. Our study sought to reveal this perspective and the importance of agroecology for the construction and promotion of sustainable territories, through the conservation of landscapes and the promotion of sovereignty and food security. This thesis consists of three scientific articles that discuss the importance of Agroecology for the conservation of landscapes, the relevance of understanding sovereignty and food security from its political perspective, and finally the analysis of the social and political processes involved in the Group's journey of Organic Hands on Earth, making a journey from the beginning of its history, the productive diversity and its importance in the maintenance of healthy territories, finally reaching the means of commercialization and economic reproduction, and the impact suffered as a result of the pandemic of Covid- 19.